Rediscovery of Osteocephalus vilarsi (Anura: Hylidae): an overlooked but widespread Amazonian spiny-backed treefrog - Ferrão, Miquéias; Moravec, Jiří; Moraes, Leandro J.C.L.; de Carvalho, Vinicius T.; Gordo, Marcelo; Lima, Albertina P. (PeerJ, 2019)
Osteocephalus vilarsi (Melin, 1941) is an Amazonian treefrog species known for over 75 years from its holotype only. Due to a lack of published data on its morphological diagnostic characters and their variations, as well as the absence of molecular, acoustic and ecological data supporting its identity, a highly dynamic taxonomic history has led this species to be confused and even synonymised with other Osteocephalus species from distinct species groups. The molecular phylogenetic relationships of O. vilarsi were investigated based on recently collected specimens from eight Northwestern Brazilian localities in the state of Amazonas, leading to its removal from the Osteocephalus taurinus species group and placement in the Osteocephalus planiceps species group. Furthermore, detailed data on morphology and colour variation are provided, as well as advertisement call and tadpole descriptions. Finally, the currently known geographic range of O. vilarsi is considerably extended, first data on the natural history of the species are provided, and the possible ecological preference of O. vilarsi for Amazonian white-sand forests is discussed.
Keywords: Amphibia; Amazonia; Brazilian biodiversity; Integrative taxonomy; Advertisement call; Tadpoles; White-sand ecosystems